“RETURNING AFRICANS TO HISTORY”: THE INTERNATIONAL PROJECT FONTES HISTORIAE AFRICANAE AND ITS CONTRIBUTION TO AFRICAN HISTORIOGRAPHY - Silvester Trnovec (Asian and African Studies)
This article is based on the introductory lecture delivered at the Sources for African History confe rence, held at the Tunisian Academy of Sciences, Letters and Art Beit al-Hikma in Carthage on 13 April 2023. At the heart of the article is the project Fontes Historiae Africanae (Sources for African History), adopted by the International Union of Academies in 1964, when African history was bre aking away from Eurocentric narratives to establish itself as an independent academic discipline. It explores the project’s foundation in the historical context following the Second World War and its impact on the development of African historiography. During the era of decolonization, efforts to reconstruct African history from an African perspective required new methodological approaches, particularly in identifying and interpreting historical sources. The Fontes Historiae Africanae project was created in response to this need, with the goal of publishing critical editions of historical sour ces, both written and oral. By focusing primarily on sub-Saharan Africa, a region long marginalized in global historiography, the project significantly contributed to revaluating Africa’s place in world history. Today, as discussions on the decolonization of knowledge and historical interpretation con tinue, Fontes Historiae Africanae remains highly relevant to current efforts to reconstruct African history.